New Emerging technology - J A Bagawade (AG Volumes, 2023)
New technologies are very important to the development of progressive businesses. The advent of new technology has aided the transition of businesses into the digital sphere. This innovation is most useful in the industrial, energy, and transportation sectors. There is always something new when the topic of technology is brought up, and the pursuit of new technologies that might benefit organizations is dogged. The eagerness to learn more about the technology and how it might change people's lives. One of the most rapidly expanding forces in the modern world is technology. There has been a dramatic shift in the fields of information technology and economic development as a result of the emergence of new technologies. This paper gives a review of the trending technologies nowadays and explores their features and applications of them.